Structural behavior of two-way slabs with large corroded area. (15th November 2019) - Said, Mahmoud E.; Hussein, Amgad A.
Highlights: This work investigated the corrosion effects on two-way slabs. An accelerated corrosion technique is used. Evaluates the structural performance under mild, moderate, and severe corrosion. The punching capacity for the slab with severe corrosion was reduced by 71.1%. The ultimate load of all corroded slabs fell below the CSA A23.3-14 design capacity. Abstract: The experimental work presented in this paper investigated the effect of large corroded area of the flexural reinforcement on the structural response of two-way reinforced concrete slabs. Four typical full-size two-way reinforced concrete slabs were fabricated and tested for this study. The slab dimensions were 1900 mm × 1900 mm × 150 mm. The reinforcement of the slabs were totally corroded except for one-half of the development length at the end of the reinforcement. The corroded area was 1480 mm × 1480 mm. A uniform level of corrosion was induced by using an accelerated corrosion technique through applying constant current density of 200 μ A / cm 2 through the reinforcement. Four different levels of corrosion were reached 0%, 15%, 25%, and 50% of the mass loss. The results are obtained in terms of load versus deflection curves, load versus crack width curves, crack patterns, deflection profiles, slab rotations, energy absorption, and ductility index. The results showed that the increase in mass loss, led to a reduction in the slab capacity and stiffness. Whereas the deflection capacities, slab rotations, and crack widths increased with increased mass loss. The experimental failure loads were compared with the predictions of four different codes. None of codes gave safe predictions for the slabs with 25% and 50% mass loss.